The role of oxidative stress in acute renal injury of newborn rats exposed to hypoxia and endotoxin. (8th August 2017) - Plotnikov, Egor Y.; Pavlenko, Tatiana A.; Pevzner, Irina B.; Zorova, Ljubava D.; Manskikh, Vasily N.; Silachev, Denis N.; Sukhikh, Gennady T.; Zorov, Dmitry B.
Abstract : Neonatal kidney injury is a frequent pathology, especially among premature infants. The search for effective nephroprotection requires the creation of adequate experimental models of nephropathy in newborns. In this study, we explored the development of acute kidney injury (AKI) in neonatal rats during hypoxia or administration of endotoxin. We found that 2‐h hypoxia (8% O2 ) and the intraperitoneal injection of 4 mg·kg −1 lipopolysaccharide (LPS) causes the appearance of AKI markers, such as kidney injury molecule‐1 (КIM‐1) and neutrophil gelatinase‐associated lipocalin (NGAL) in the rat urine after 24 and 72 h of exposure. On the other hand, the levels of blood urine nitrogen under the same conditions rise only slightly. The damaging effects of hypoxia and endotoxin were accompanied by histological changes in the renal tissue and a significant decrease in the proliferation marker, (proliferating cell nuclear antigen). It is revealed that 3 h after the introduction of LPS, levels of reactive oxygen species in the kidney were significantly increased, and the injection of the antioxidant N ‐acetylcysteine afforded protection from AKI, evaluated by urine КIM‐1 and NGAL levels. Thus, the simulation of AKI in newborn rat pups can be employed in screening for potential nephroprotective drugs, particularly among antioxidative compounds to be used in neonatology. Abstract : Hypoxia and lipopolysaccharide (LPS) injection caused acute kidney injury (AKI) in neonatal rats, an increase in damage markers, kidney injury molecule‐1 (KIM‐1), and neutrophil gelatinase‐associated lipocalin (NGAL) in urine and a decrease in proliferation and regeneration markers [proliferating cell nuclear antigen (PCNA) and growth differentiation factor 11 (GDF11)] in kidney tissue. LPS induced oxidative stress in neonatal kidney and the injection of the antioxidant N ‐acetylcysteine afforded protection from AKI caused by these factors.